Using carboxymethyl gum from Tamarindus indica and Cassia fistula seeds with Chromolaena odorata leaf extract to develop antibacterial gauze dressing with hemostatic activity - Wancheng Sittikijyothin; Bussaba Phonyotin; Tanikan Sangnim; Kampanart Huanbutta (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Gauze dressing is a barrier against microbial infection in wounds. The seed gums of Tamarindus indica and Cassia fistula are abundant in tropical countries; we used them as a coating material of cotton gauzes to improve the liquid absorption ability. Moreover, Chromolaena odorata leaf extract was loaded on the gums for antibacterial gauze dressing with hemostatic activity. Experimental approach: Crude gums were extracted from T. indica and C. fistula seeds and carboxymethyl gums were then derived and chracterized. C. Odorata ethanolic extract was also prepared by maceration and its antimicrobial and blood clotting activities were determine coated gauze dressing containing different concentrations of carboxymethyl gum was prepared in the presence of various concentrations of C. odorata extract. Then, the physical properties, antibacterial activity, and skin-irritating effects of the coated gauze were analyzed. Findings/Results: The results indicated that the amount of carboxymethyl gum affected the physical properties and absorption capacity of the coated gauze. C. odorata extract exhibited better bactericidal activity against Staphylococcus aureus than against Escherichia coli. The blood clotting effects of C. odorata extract indicated that it had dramatic hemostatic efficacy. The coated gauze exhibited bactericidal activity against S. aureus. In the human skin irritation test, the coated gauze caused no adverse effects on human skin. Conclusion and implication: Coated gauze has the potential to serve as a prototype for primary hemostasis in first aid for opened wounds such as abrasions and lacerations.